THE RELATIONSHIP BETWEEN SERVICE QUALITY AND CUSTOMERS’ PURCHASE INTENTION OF BAKERY-THEMED CAFES IN BANDUNG - Putri, Nadila Vedania; Aprianingsih, Atik (Journal of Business and Management, 2017)
Abstract. Bakery themed café is the type of café, which also sell bakery products. By the fact of the changing in the food and lifestyle preferences of people who lives in Bandung, the development of bakery themed cafés are also rapidly happened. Therefore, the factors that affected customers’ purchase intention of bakery themed café in Bandung is need to be analyzed. Service is the key influences of forming customers’ purchase intentions in service environments. This research attempts to investigate the customers’ current perception and to identify the relationship between service quality and customers’ purchase intention of bakery themed café in Bandung. Online questionnaires using Likert Scale designed for 200 respondents with judgmental sampling method. Multiple Regression Analysis used to measure the relationship between service quality with customers’ purchase intention. The result shows that service quality is having the positive relationship with customers’ purchase intention of bakery themed café in Bandung. The service quality also significantly impact purchase intention of bakery themed café. This study is expected to provide a valuable result regarding the relationship between service quality and customers’ purchase intention in bakery themed café in Bandung and to form a suitable marketing strategy to be applied.  Keywords: Service Quality, Customers’ Purchase Intention, Bakery-themed Café, Service Marketing